"Getting Rid of Junk" (Zien Journal of Social Sciences and Humanities, 2023)
This article consists of a collection of ideas and opinions aimed at making people feel good, focused on finding ways to find anyone's heart when necessary. On behavioral science theories to better understand the influence of human factors in cybersecurity.